Hurricane Katrina Lessons for Army Planning and Operations - Davis, Lynn E. (RAND Corporation, 2007)
The efforts undertaken by civilian and military organizations in response to Hurricane Katrina were historically unprecedented, but a number of changes would enhance future Army and National Guard disaster-response efforts, including preparing governors to call up Guard units for out-of-state emergencies and the creation of regional standing homeland security task forces.